(untitled) (مجلة جامعة بابل للعلوم الانسانية, 2018)
The crimes are different according to the different crimes, some of them are limited to traditional elements because they are consistent with the nature of the crime committed, including the need to add a special corner to the character of the actor and based on that idea, the crime of exploiting the job is not limited to traditional elements, but must be preceded by a special corner is the perpetrator, The law requires the offender to have a special status through which or through which to commit this crime. This is stated in the provisions of the Iraqi Penal Code No. (111) of 1969, the amendment of which indicates that the crime of exploiting the job is based on three The second element is the physical element of the conduct of the exploitation of the job and the obtaining of an illegal benefit or benefit under the public service, and the third pillar is the moral pillar (Criminal intent), especially that the crime of exploitation of the job is not limited to a specific country or society without a specific or a certain period of time, but rather linked this crime in various forms of the existence of human society has formed this crime is important and dangerous at various levels and in each country The world has called for the need to develop the appropriate legal formulas to deal with the provisions of this crim.